Design of Mechanics and Locomotion System For Box Culverts Inspection Robot - Anwar, Khoirul; Juliarsyah, Mohammad Rizanto; Pungkiarto, Irwanda Yuni; Mohammad Abdullah (AI Society & STMIK Indonesia, 2025)
In Indonesia there is often a flood caused by continuous heavy rain, based on the observation of the condition of the culprit is the cause of flooding in Indonesia. One of the problems owned by the public Works office today is the presence of Dutch-made sewers with concrete materials that have a depth of 6 meters below the surface so that the workers are hard to reach. The following problems need to be developed a technology that does not require human presence to directly monitor the circumstances that occur in the drain pipes (sewers) by using a mobile robot to perform monitoring. The result of this study obtained output in the form of a mobile robot that can work in various terrain, and to get a good response in the control system used Ziegler-Nichols for Tunning.